Enhanced X-ray reflectivity from Pt-coated silicon micropore optics prepared by plasma atomic layer deposition. (4th August 2020) - Ishi, Daiki; Ezoe, Yuichiro; Ishikawa, Kumi; Numazawa, Masaki; Fukushima, Aoto; Otsubo, Ryota; Suzuki, Hikaru; Yuasa, Tatsuya; Sakuda, Sae; Uchino, Tomoki; Fujitani, Maiko; Mitsuda, Kazuhisa; et al.
Abstract: We report the enhancement of Pt-coated silicon micropore X-ray optics using plasma atomic layer deposition (ALD). High-aspect-ratio micropores of width 20 μ m and depth 300 μ m were coated with ∼20 nm Pt and ∼10 nm Al2 O3 . The estimated surface roughnesses, determined from X-ray reflectivity curves for Al K α 1.49 keV radiation, were 1.2 − 1.0 + 0.6 and 1.6 ± 0.1 nm rms before and after the plasma ALD, respectively. The plasma ALD-coated Pt film shows no significant change compared to the underlying silicon and better surface roughness than our previous study of thermal ALD. We also discuss future improvements with plasma ALD.